Manifest madness mental incapacity in the criminal law - Loughnan, Arlie (Oxford : Oxford University Press, 2012)
Understanding mental incapacity in criminal law is notoriously difficult; it involves tracing overlapping and interlocking legal doctrines, current and past practices of evidence and proof, and also medical and social understandings of mental illness and incapacity. With its focus on the complex interaction of legal doctrines and practices relating to mental incapacity and knowledge - both expert and non-expert - of it, this book offers a fresh perspective on this topic.
Specialized.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Mentally ill offenders -- Legal status, laws, etc. -- England; Mentally ill offenders -- Legal status, laws, etc. -- Wales; Criminal liability -- England; Criminal liability -- Wales; Insanity (Law) -- England; Insanity (Law) -- Wales; Law; Laws of specific jurisdictions & specific areas of law